Your Farm Weather Station: Installation and Maintenance Guidelines - Clyde W. Fraisse; George W. Braun; William R. Lusher; Lee R. Staudt (EDIS, 2015)
Weather is a prominent factor in the success or failure of agricultural enterprises, and the technology has improved and is less expensive, so many farmers are installing farm-based weather stations for tracking weather conditions, scheduling irrigation, making decisions related to cold protection, and accomplishing other tasks. But management decisions must be based on high-quality observations. Sensors must meet accepted minimum accuracy standards, and the station must be sited properly and well-maintained. This 5-page fact sheet provides farmers with basic guidelines for installing and maintaining a weather station. Written by Clyde W. Fraisse, George W. Braun, William R. Lusher, and Lee R. Staudt, and published by the UF Department of Agricultural and Biological Engineering, April 2015.